Bamboleo - Garcia; Warner Music (Germany). (Germany : Warner Music Germany, 1997)
Contains four Eurodance tracks with Latin themes.
CD 1 : Radio edit / (3:48) -- Bambo mix / (5:35) -- Extended mix / (4:57) -- Full-Moon-Mix / (6:49).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English